PENGARUH PENGGUNAAN MEDIA PEMBELAJARAN MACROMEDIA FLASH TERHADAP HASIL BELAJAR SISWA PADA MATERI LAJU REAKSI KELAS XI IPA SMA MUHAMMADIYAH 1 KETAPANG - Dwi Rindha Adiansyah (Universitas Muhammadiyah Pontianak, 2018)
This study aimed at investigating the influence of macromedia flash to student learning achievement at SMA Muhammadiyah I Ketapang. The use of this learning media aimed to facilitate teachers in conveying learning material so that students are effectively able to achieve the learning goals. The population of this study were 20 students of the eleventh grade of Natural Sciences class of SMA Muhammadiyah I Ketapang . The sample was Natural Science class students consisted of 10 students as the experimental class and 10 students as the control class. Using a quasi-experimental, this study used test questions of reaction rate material as the instruments. The study revealed a significant difference between experimental class taught using macromedia flash and control class without the media. This was shown by the results of the data analysis of the t-test obtained by the t-value of 2.682 greater than the 5% table value of 2.100. Further, the experimental class taught by using flash macromedia showed an average value of 81.11, and the control class showed an average value of 63.33. In conclusion, flash media was effective in improving student learning outcomes, by the score difference of 17.78.